The unequal battle against infertility - Groes, Fane,Houstecka, Anna,Iorio, Daniela,Santaeulàlia-Llopis, Raül (Centre for Economic Policy Research, 2024)
Using Danish administrative data, we show that IVF success is associated with maternal education: College-educated women have a 9% higher live birth chance than high school-educated women and 25% higher than dropouts. We exclude infertility causes, health, clinics, finances, and partner attributes as drivers. Instead, we focus on latent factors like ability and psychological traits. First, we show how proxies for these factors like Grade Point Average (GPA) shape IVF success. Second, we build a dynamic model of post-IVF-failure dropout where women differ in latent ability and psychological costs. Our model counterfactuals imply that ability explains 87% of the education gradient in IVF success, prompting a policy discussion.
https://cepr.org/publications/dp18766
Keywords: Graue Literatur; In-Vitro Fertilization; Success; Inequality; Infertility; Education; Ability; Admin-istrative Data; Endogenous Dropouts